2022
DOI: 10.1523/jneurosci.0914-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and Stochastic Components of Cortical Down States: Dynamics and Modulation

Abstract: Slow oscillations are an emergent activity of the cerebral cortex network consisting of alternating periods of activity (Up states) and silence (Down states). Up states are periods of persistent cortical activity that share properties with that of underlying wakefulness. However, the occurrence of Down states is almost invariably associated with unconsciousness, both in animal models and clinical studies. Down states have been attributed relevant functions, such as being a resetting mechanism or breaking causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…From this common description, we derive characterization metrics that are agnostic about the data’s origins. Such a generalized approach may be applied to different types of propagating fluctuating activity associated with different brain states, including various expressions of slow waves 54 , 55 (as we do here), burst suppressions, 56 , 57 or waves in higher frequencies. 58 , 59 This way, we arrive at relatable wave characterizations and avoid comparing apples to oranges ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…From this common description, we derive characterization metrics that are agnostic about the data’s origins. Such a generalized approach may be applied to different types of propagating fluctuating activity associated with different brain states, including various expressions of slow waves 54 , 55 (as we do here), burst suppressions, 56 , 57 or waves in higher frequencies. 58 , 59 This way, we arrive at relatable wave characterizations and avoid comparing apples to oranges ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the Down state duration increased with the duration of Up states, albeit at a slower rate. This can be partially explained because Down states have an activity-dependent component which can be mediated largely by hyperpolarizing currents, probably potassium currents 6,9 . Indeed, previous experimental and computational studies have revealed a dynamic link among Up state and Down state durations 8,24,26,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Slow oscillations, characterized by interspersed Up and Down states, are thus a hallmark of both intact and isolated cortical networks. Up states, periods of persistent firing, arise from recurrent excitation and network reverberation, while Down states (silent periods) are triggered by the build-up of inhibitory currents during Up states [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%

H-current modulation of cortical Up and Down states

Dalla Porta,
Barbero-Castillo,
Sanchez-Sanchez
et al. 2024
Preprint
Self Cite
“…Slow wave activity is a state of cortical bistability, characterized by the spontaneous and almost periodic emergence of Up (active; neuronal depolarization and firing) and Down (silent; neuronal hyperpolarization) states, in which network interactions are disrupted [ 11 ], complexity is low [ 12 , 13 ], synchrony is high [ 14 ], and information processing is therefore impaired. In order for cortical circuits to be in an asynchronous state that can process information [ 15 ] the system should leave the slow wave attractor [ 16 , 17 ] and recover spatiotemporal dynamics and properties that support wakefulness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%